HUKUM ISLAM MEMAKNAI SHOPEEPAYLATER DALAM MEMENUHI KEBUTUHAN KELUARGA - Yolanda Destiana (ISLAMITSCH FAMILIERECHT JOURNAL, 2023)
Abstract : This article discusses the shopeepaylater payment method in meeting family needs according to Islamic Law. Shopeepaylater is one of the latest innovations from shopee, where people can receive goods first and then make payments. With the existence of this shopeepaylater, Indonesian people are greatly helped to meet family needs, from primary needs to secondary needs. However, the Muslim community has slightly forgotten the Islamic Law contained in the shopeepaylater. In Islamic Law literature, there are various forms of business cooperation transactions, both commercial and social, one of which is in the form of "alqardh". Al-qardh is the provision of assets to others that can be collected or requested again without expecting rewards or in other words, it is a lending and borrowing transaction without additional conditions at the time of returning the loan. This shopeepaylater work system is still not in accordance with Islamic Sharia Law (Alqardh) because interest is still charged when choosing an installment payment and a fine is charged if the payment exceeds the given maturity period.